2022
DOI: 10.1038/s41467-022-35351-w
|View full text |Cite
|
Sign up to set email alerts
|

Multistep diversification in spatiotemporal bacterial-phage coevolution

Abstract: The evolutionary arms race between phages and bacteria, where bacteria evolve resistance to phages and phages retaliate with resistance-countering mutations, is a major driving force of molecular innovation and genetic diversification. Yet attempting to reproduce such ongoing retaliation dynamics in the lab has been challenging; laboratory coevolution experiments of phage and bacteria are typically performed in well-mixed environments and often lead to rapid stagnation with little genetic variability. Here, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 84 publications
3
21
0
2
Order By: Relevance
“…This is similar to past work where more homogenous environments accelerated the coevolution of bacterial resistance with phages (Brockhurst et al 2003). Additionally, we found that evolved populations in our local phage treatment maintained phage susceptibility that could enable coexistence of bacteria and phages (Fig 3), consistent with past work that spatial structure and heterogeneity increases host-parasite coexistence (Brockhurst et al 2006;Tamar and Kishony 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to past work where more homogenous environments accelerated the coevolution of bacterial resistance with phages (Brockhurst et al 2003). Additionally, we found that evolved populations in our local phage treatment maintained phage susceptibility that could enable coexistence of bacteria and phages (Fig 3), consistent with past work that spatial structure and heterogeneity increases host-parasite coexistence (Brockhurst et al 2006;Tamar and Kishony 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Changes in the Klebsiella capsule are a primary mechanism of resistance to temperate phages, as shown for virulent phages ( Hesse et al, 2020 ; Tan et al, 2020 ; Cai et al, 2019 ; Majkowska-Skrobek et al, 2021 ). More broadly, fast inactivation of the capsule confirms that alteration of the host recognition determinants frequently results in the protection of bacterial populations against phage ( Mutalik et al, 2020 ; Westra et al, 2015 ; Shaer Tamar and Kishony, 2022 ). However, after six days of co-evolution, the frequencies of both strains in MMC reached an equilibrium.…”
Section: Discussionmentioning
confidence: 74%
“…Although we were able to characterize the molecular underpinnings of major features of the interaction network, we also note that more phenotypic and genomic variation exists which we have yet to explain, further highlighting the complexity that can evolve rapidly (i.e., within 100 to 200 generations). Although the molecular mechanisms identified in our flasks will differ across vastly different taxa and ecological communities ( 24 , 34 ), our work demonstrates how inherent coevolutionary processes can give rise to complex patterns that abound in natural ecosystems.…”
Section: Discussionmentioning
confidence: 94%
“…More broadly, previous observations of geographically isolated modules have suggested that spatial separation assists in the formation of such patterns (5,8,9,24). Although spatial structure certainly plays an important role in generating and maintaining diversity (35), it is also possible that modules may form in sympatry, and then separate in space over time.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation